Non-Timber Forest Products and Sustainable Forest Management in Nigeria (2005)
"The paper examines the potential roles of non-timber forest products in sustainable forest management in Nigeria. It is observed that there are numerous non-timber forest products in the various ecological zones of the country. Presently the situation of the nations’ forests is far from being sustainable. Case's of illegal felling, forest encroachment, poaching and outright de-reservation of gazetted forest reserves are very rampant. The forest reserve communities have become very hostile and uncooperative towards forest management and conservation programmes. Multiple-use forest management has been found very useful in achieving sustainable forest management in many parts of the world. The country’s rich biodiversity, prevalence of consequences of environmental mismanagement, insecurity of forest properties, and the nature of traditional indigenous land resources management systems in the country all provide a useful platform upon which the development of multiple- use forest management could be built. Since Multiple-use forest management involves the management of forests such that all its resources are considered in planning the management, it is obvious that non-timber forest products have a crucial role to play in sustaining the resources of our forests. To make progress in this direction, it is necessary to first carry out a needs survey of forest communities, undertake detailed resource inventory, hold stakeholders’ meetings and engage in both socio-economic and ecological studies so as to evolve a socially acceptable, economically viable and ecologically sound management technique."